An Investigation of Students’ Language Learning Strategies Used in Mastering Speaking Skill - Aswin Abbas (Universitas Cokroaminoto Palopo, 2014)
This research aimed to investigate the students’ language learning strategies used in mastering speaking skill by the students in mastering speaking skill. The researcher applied mixed method research, Qual-quan model. The Population of this research was the fourth semester students of English and Literature Department of UIN Alauddin Makassar. The Sample was the fourth semester students of English and Literature department, which consist of 15 students choosed randomly. This research used simple random sampling technique. This research applied think aloud and questionnaire as the instrument. The result of this study showed that students’ language learning strategies used in mastering speaking skill were (1) memorizing vocabularies and using picture categorized as memory strategies (2) listening to the music, watching English video, watching English movie, watching English TV program, listing difficult vocabularies, using dictionary, practicing, reading English text, speaking alone, repeating, guessing, doing conversation, repeating were categorized as cognitive strategies (3) Joining the club meeting and getting course, were categorized as metacognitive strategies (4) using similar word was categorized as compensation strategies. (5) Speaking with their friend and speaking alone or herself were categorized as social strategies and (6) discussing problem was categorized as affective strategies.